Fairness measurement on procedural justice for policy making in Taiwan: A comparative study of Cijin Seaside Park and Tamsui Fisherman's Wharf - Yu-Tien Huang; Ming-Shen Wang (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
Public policies in a pluralistic society should be able to clarify and cope with the complicated nature of public issues dominated by multiple parties, multiple values, and subjective judgment. Therefore, instead of merely concluding with the outcome, we should also take input into account when evaluating resource allocation or assessing policy effectiveness. This research adopted fairness measurement approach of the Information Integration Theory (IIT) to analyze Cijin Seaside Park and Tamsui Fisherman's Wharf in Taiwan, and conducted procedural justice for policy-making. This dimension of procedural justice was based on the designs of input and outcome; the input was policy support and the outcome used the level of administrative cooperation as an assessment indicator. Twenty local merchants and twenty tourists were purposively sampled from each site. The study results indicated that the local merchants in both Cijin Seaside Park and Tamshi Fishers' Wharf fit the unequal-weight averaging rule of policy support factor. They also fit the unequal-weight averaging rule of the administrative cooperation factor. As for the tourists, those in both Cijin Seaside Park and Tamshi Fishers' Wharf fit the unequal-weight averaging rule of policy support factor. Also, they fit the unequal-weight averaging rule of the administrative cooperation factor.
Keywords: D63; D78; L88; 330; Fairness measurement; Information Integration Theory; policy-making; procedural justice; resource allocation